An Update on the Relationship of SARS-CoV-2 and Male Reproduction - Guo, Juncen; Sheng, Kai; Wu, Sixian; Chen, Hanxiao; Xu, Wenming (Frontiers in Endocrinology, 2021)
Since the outbreak of the COVID-19, up to now, infections cases are continuously rising to over 200 million around the world. Male bias in morbidity and mortality has emerged in the COVID-19 pandemic. The infection of SARS-CoV-2 has been reported to cause the impairment of multiple organs that highly express the viral receptor angiotensin-converting enzyme 2 (ACE2), including lung, kidney, and testis. The adverse effects on the male reproductive system, such as infertility and sexual dysfunction, have been found an association with COVID-19. This causes a rising concern among couples intended to have a conception or need assisted reproduction. To date, a body of studies explored the impact of SARS-CoV-2 on male reproduction from different aspects. This review aims to provide a panoramic view to understand the effect of the virus on male reproduction and a new perspective of further research for reproductive clinicians and scientists.